Function follows flood: how flooding affects the architectural mitigation and adaptation response of Sitio Fisheries, barangay Malued, Dagupan City. - Solano, Joemel Palsimon; Johannes Vincent Chua (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
One major natural disaster that can cause large-scale destruction, human casualties, and financial losses is flooding. Due to earth subsidence and rising sea levels, Dagupan City, which is situated on the eastern margin of the Agno River delta, is predicted to be submerged in 15 years. Good design may reduce the vulnerability of the built environment to floods by improving the ability of structures to manage water and providing protection against possible dangers. The purpose of this thesis is to determine a baseline study and examine how architectural patterns respond to the recurrent floods and the impact of yearly flooding on structures. Additionally, it looks into how building owners, architects, and other professionals in the built environment have responded to the continual development and elevation of the city roads, and how this has affected building typology and building use.
This thesis primarily examines Dagupan City's current residential structures, with a specific emphasis on those in Sitio Fisheries in Barangay Malued that are expected to experience immediate flooding. The review of related literature discusses strategies in design to study emerging architectural forms that may endure floods. The comments made by the key informant interviews were examined in order to determine the motivators and barriers influencing their comprehension and application of flood management in their design.
Include appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman$dJanuary 2024xv
Keywords: Built environment -- Dagupan City; Floods -- Dagupan City